Comparative Analysis of Global Proteome and Lysine Acetylome Between Naive CD4+ T Cells and CD4+ T Follicular Helper Cells - Zhao, Ming; Jia, Sujie; Gao, Xiaofei; Qiu, Hong; Wu, Ruifang; Wu, Haijing; Lu, Qianjin (Frontiers in Immunology, 2021)
As a subgroup of CD4+ T helper cells, follicular helper T (Tfh) cells help to germinal center B cells and mediate the development of long-lived humoral immunity. Tfh cells dysregulation is associated with several major autoimmune diseases. Although recent studies showed Tfh cells differentiation is controlled by the transcription factor Bcl6, cytokines and cell-cell signals, limited information is available on the proteome and post-translational modifications (PTM) of proteins in human Tfh cells. In this study, using TMT labeling technique, antibody-based affinity enrichment and high-resolution LC-MS/MS analysis, we investigated quantitative proteome and acetylome in human naive CD4+ T cells and in vitro induced Tfh (iTfh) cells. In total, we identified 802 up-regulated proteins and 598 down-regulated proteins at the threshold of 1.5 folds in iTfh cells compared to naive CD4+ T cells. With the aid of intensive bioinformatics, biological process, cellular compartment, molecular function, KEGG pathway and protein-protein interaction of these differentially expressed proteins were revealed. Moreover, our acetylome data showed that 22 lysine acetylated proteins are up-regulated and 26 lysine acetylated proteins are down-regulated in iTfh cells compared to the naive CD4+ T cells, among which 11 differentially acetylated lysine residues in core histone were identified, indicating proteins acetylation and epigenetic mechanism are involved in regulating Tfh cells differentiation. Our study provides some important clues for investigating T cells activation and Tfh cells differentiation.